Isolation and Identification of Intestinal parasites and protozoa from Flesh flies Sarcophaga africa in Baghdad - Hadi, Afkar M (Al-Nahrain Journal of Science, 2018)
A study was conducted to determine the role of flesh flies Sarcophaga africa as carriers of intestinal parasites in different locations of Baghdad as a primary efforts in Iraq from March to October 2011.A total of 140 Sarcophaga africa were examined both the external and internal to identify the parasites. The parasites were transmitted exterinally: (Paramphistomum sp.10.7%, Ascaris vitulorium 7.8%, Strongyloides westri 5%, Taenia sp. 10.6%). The parasites were transmitted internally: (Trichuris sp.2.8%, Toxocara sp.20% and Ascaris lubrecoides12.8%, Cryptsporidium parvum17.8%,Cryptsporidium muris 8.5%, Cyclospora cayetanensis 6.8%, Thieleria sp. 5% and Trypanosoma sp. 2.1%). It was observed that more parasites were isolated from gut contents than the external surfaces of the flies examined (P  0.01). The public health significance of these findings is highlighted.